2001
DOI: 10.1074/jbc.m105418200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor (ER)-α, but Not ER-β, Mediates Regulation of the Insulin-like Growth Factor I Gene by Antiestrogens

Abstract: The importance of insulin-like growth factor I (IGF-I) on maintenance of skeletal integrity has been widely recognized. Although osteoblasts secrete some IGF-I, the liver is the primary endocrine source for IGF-I. We have studied the regulation of the human IGF-I promoter in the hepatocyte cell line Hep3B, and we have shown that the IGF-I promoter, when co-transfected in Hep3B cells together with an estrogen receptor (ER)-␣ expression vector, was transcriptionally regulated by raloxifene or raloxifene-like mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…Experimental data have indeed shown that TAM suppresses liver IGF-I gene expression (19) and that IGF-I promoter on the hepatocyte cell line Hep3B is transcriptionally regulated by RAL after transfection with estrogen alpha-receptor (20).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data have indeed shown that TAM suppresses liver IGF-I gene expression (19) and that IGF-I promoter on the hepatocyte cell line Hep3B is transcriptionally regulated by RAL after transfection with estrogen alpha-receptor (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the release of IGF-I into luminal fluid was abolished by ICI 182,780 treatment, demonstrating an ER-mediated regulation of IGF-I production and secretion. Although ICI 182,780 usually results in an attenuated cellular response of E 2 via antagonism at both ER subtypes (21), extensive work has been performed suggesting that estrogen-mediated regulation of IGF-I is mainly through ER␣ and not through ER␤ in culture cell lines in vitro (13,62) and in rat uterus in vivo (27). Thus our findings indicate that the functional significance of ER␣ is closely related to IGF-I regulation in mouse fallopian tube tissues and fluid in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Animals with null mutations in genes for either ER or ER show distinct skeletal abnormalities (Korach et al 1996, Lindberg et al 2001, Windahl et al 2001. Furthermore, distinct signal pathways can be activated by ER and ER (Jones et al 1999, Shapiro et al 2000, Fournier et al 2001. In terms of responses in differentiating osteoblastic cells, a recent report documents distinct regulation by ER or ER in stably transfected immortalized fetal osteoblastic cells resulting in differing regulation of select genes (Waters et al 2001).…”
Section: Figurementioning
confidence: 99%